Reminiscences - Transformations - Quests : Painting - sculpture - engraving. (Athene, : Ministry of Culture and Sciences, 1985)
Adamacos, Yannis ; Vacalo, George ; Varotsos, Constantinos ; Vassiliou, Spyros ; Venetoylias, Lucas ; Gaïtis, Yannis ; Yioldassis, Dimitris ; Golfinos, George ; Gounaropoulos, George ; Decoulakos, Ilias ; Engonopoulos, Nikos ; Theofilactopoulos, Makis ; etc.
Reminiscences - Transformations - Quests : Painting - sculpture - engraving, Athene, 1985
boek